2010
DOI: 10.1073/pnas.0906384107
|View full text |Cite
|
Sign up to set email alerts
|

Interactome analysis of longitudinal pharyngeal infection of cynomolgus macaques by group A Streptococcus

Abstract: Relatively little is understood about the dynamics of global hostpathogen transcriptome changes that occur during bacterial infection of mucosal surfaces. To test the hypothesis that group A Streptococcus (GAS) infection of the oropharynx provokes a distinct host transcriptome response, we performed genome-wide transcriptome analysis using a nonhuman primate model of experimental pharyngitis. We also identified host and pathogen biological processes and individual host and pathogen gene pairs with correlated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The use of different transactivating ligands and receptors by SMC could provide a means to adapt inflammatory responses to the type of injury. EGFR/ErbB1 sensing could be more important to the binding and clearance of bacteria (31), whereas the initiation of inflammation after acid exposure might require ErbB4 signaling, which is important for surfactant production and proliferation of lung epithelial cells (32). Moreover, we found that IL-1b induced CXCL8 release by htSMC in an ADAM17-NRG1-dependent manner.…”
Section: Discussionmentioning
confidence: 72%
“…The use of different transactivating ligands and receptors by SMC could provide a means to adapt inflammatory responses to the type of injury. EGFR/ErbB1 sensing could be more important to the binding and clearance of bacteria (31), whereas the initiation of inflammation after acid exposure might require ErbB4 signaling, which is important for surfactant production and proliferation of lung epithelial cells (32). Moreover, we found that IL-1b induced CXCL8 release by htSMC in an ADAM17-NRG1-dependent manner.…”
Section: Discussionmentioning
confidence: 72%
“…As a consequence, we have extensively used non-human primates, the most human-relevant animal model possible, as the preferred host for testing hypotheses bearing on GAS molecular pathogenesis. 13,14,34,[37][38][39] However, high cost and substantial…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests an increased interest in performing GAS gene expression studies under human-relevant in vitro conditions or during in vivo infections. 14,37,[46][47][48][49] Infected hemolymph is easy to manipulate and enriched in GAS cells relative to host cells. This helps to overcome the challenges associated with extracting a sufficient quantity of high quality GAS RNA from infected animal tissues for TaqMan or expression microarray analyses.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Genechip Experiment-RNAs were extracted and DNA microarray targets were prepared as described previously (27). Gene expression was measured using the Affymetrix 430 2.0 Genechip containing the mouse genome and data analysis were carried out as described previously (28) with the following modifications.…”
Section: Rna Isolation and Real Time Pcr (Rt-pcr)mentioning
confidence: 99%